Design Development and Simulation of a Continuous Extrusion Machine Setup - Sinha, Devendra kumar (My University, 2015)
The Continuous Extrusion (CE) forming process uses natural frictional force between a circular driving wheel and material to produce sufficiently long continuous products. Variety of sectional shapes which is hard to produce by classical forming processes is produced by Continuous Extrusion. There exists variety of versions of CE process. The Continuous Extrusion process is better than the conventional extrusion process in many ways such as: (i) The input material can be used in varied forms such as coiled rod, molten metal and powder material. (ii) Tooling’s preheating and homogenizing are not needed. (iii) Manpower requirement for running CE is low. (iv) Tooling cost and their maintenance cost is also low. (v) Products can be obtained in cut lengths and in continuous coil form. (vi) Products such as refrigeration tubes and very thin tubes are well produced. (vii) Scrap rate is reduced. Because of its superiority and impact on the current forming technology, demand of products produced by CE from industry has been growing rapidly. Better surface quality, reduced effective stresses are some of the benefits of Continuous Extrusion process in comparison to conventional extrusion process. The analysis and performance of the Continuous Extrusion process depends on various factors such as peripheral speed of extrusion wheel, extrusion ratio and size of flash gap, wheel groove and shoe surface conditions etc. The study area of continuous extrusion can be categorized into four main branches as: (i) conceptual design, development steps, (ii) concepts of Continuous Extrusion process, (iii) experimental study on different metals and alloys especially for Aluminum Al 1100, (iv) industrial applications. Conceptual design is the key activity in early product design and development (PDD). PDD determines the product functions, forms and the basic structure. Major manufacturing cost is committed in early conceptual design process. The steps of conceptual product development process may be mentioned as: (i) preliminary idea and sketching the concept idea, (ii) preliminary design and alternatives, (iii) feasibility study, (iv) feasibility alternatives, (v) detailed design, (vi) component generation and (vii)functional study. In recent time this is facilitated by CAE modeling and analysis and subsequently final freeze design and manufacturing. A better way to study the behavior of Continuous Extrusion process for non-ferrous materials such as Aluminum, Copper and Brass is by means of Computer Aided Engineering based procedure. The technology of product manufacturing by Continuous Extrusion process is developing very fast to shape complex profiles of products. There have been a lot of investigations about Continuous Extrusion process. Most of them involve finite element simulations using finite element method and CAE activities (Computer Aided Engineering) corresponding to rod and tube extrusions. Only few investigations in the field of Continuous extrusion process relates to surface separation and curling phenomenon, analysis of flash formation and measurement of flash gap size. Very few experimental studies have been carried out related to continuous extrusion of Aluminum alloy with the deformation behavior and material characterization. Different areas of research in Continuous Extrusion have been identified and detailed literature survey has been categorically presented It is observed from the literature that there is no investigation carried out related to metallurgical, manufacturing and optimization aspects together on Continuous Extrusion process. In this thesis most of the work is being introduced and scope of the present work has been highlighted. There have been several challenges such as optimization of process parameters in Continuous Extrusion process of nonferrous materials such as Aluminum and Copper feedstock materials and its experimental study. Microstructure analysis of extruded product in Continuous Extrusion process is an area, still to be explored in the field of Continuous Extrusion process. The work proposed in this thesis is an attempt to study Continuous Extrusion of Aluminum and Copper feedstock material so as to generate enough knowledge and make it avail of the technology for industry applications.As the summary, the following topics of interest are presented: a) Literature review of Continuous Extrusion process, FEM simulation and Optimization. b) Modeling, CAE simulation, parametric study and analysis of Continuous Extrusion process for Aluminum and Copper feedstock materials using different sizes of die and friction conditions. c) Design modification and Optimization of Continuous Extrusion process. d) Design, Development and Fabrication of a Continuous Extrusion machine setup for 9.5 mm feedstock material. e) Experiments and testing on the machine setup: for Aluminum feedstock material (9.5 mm diameter) under different combinations of extrusion wheel speed and extrusion ratio and some parametric study (Total Load vs Wheel speed, Total Load vs Extrusion ratio). f) Validation & comparison of simulation and experimental results for Aluminum and Copper feedstock materials. g) Investigation on microstructural analysis: before and after extrusion using Light Optical Microscopy (LOM). h) Investigation on strength of Extruded products: tensile and hardness test of feedstock material before and after extrusion. i) The optimization of CE process parameters The above work has been organized in seven chapters
Keywords: Extrusion Machine; Design Development